(untitled) (American Journal of Life Science and Innovation, 2022)
Lipases are a class of hydrolytic enzymes that catalyze the hydrolysis of insoluble triacylglycerol to glycerol, acylglycerols, and free fatty acids. The present study is aimed at identifying Lipase producing bacteria isolated from soil determining the optimal conditions (temperatures, pH, and metal ion concentrations) of Lipases produced through submerged fermentation by bacteria of different three (3) genera. The different bacterial isolates with good hyper-producing potentials for Lipases were identified by Polymerase Chain Reactions (PCR). The effect of temperature on cellulase activity was determined by estimating the lipase activity at pH 9.0 within a temperature range of (300C-600C). In order to determine the behaviour of the enzymes within some metallic ions, the reaction of the enzyme and gum Arabica/olive oil mixture was allowed to proceed at 500C with duplicate test tubes containing 50mM CaCl2 (Ca2+). MgSO4 (Mg 2+), Nacl(Na+), Kcl (K+). The identifies of the lipase producing bacteria were identified as Brevibacterium brevis strains Hk 544, Pseudomonas aeruginosa strain WES, Bacillus megaterium strain WH13, and Bacillus subtilis strain BS 01 for Isolate H, A, B and F., respectively. Optimum temperatures for the activities of Brevibacterium brevis strains Hk 544, Pseudomonas aeruginosa strain WES, Bacillus megaterium strain WH13, and Bacillus subtilis strain were determined to be 50oC, 50oC , 45oC and 45oC, respectively. Optimum pH for the activities of Brevibacterium brevis strains Hk 544, Pseudomonas aeruginosa strain WES, Bacillus megaterium strain WH13, and Bacillus subtilis strain were determined to be alkaline (8.0 to 9.0). The observation that sodium and potassium ions at 50mm concentration enhanced the activity of some of the lipases under this investigation showed that sodium and potassium are likely to be co-factors for the performance of these lipases.